2012
DOI: 10.1111/tmi.12014
|View full text |Cite
|
Sign up to set email alerts
|

In vivo susceptibility to benznidazole of Trypanosoma cruzi strains from the western Brazilian Amazon

Abstract: Abstractobjective To assess the susceptibility of Trypanosoma cruzi strains from Amazon to benznidazole. methods We studied 23 strains of T. cruzi obtained from humans in the acute phase of Chagas disease, triatomines and marsupials in the state of Amazonas and from chronic patients and triatomines in the state of Paraná , Brazil. The strains were classified as TcI (6), TcII (4) and TcIV (13). For each strain, 20 Swiss mice were inoculated: 10 were treated orally with benznidazole 100 mg/kg/day (TBZ group) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
4
41
1
2
Order By: Relevance
“…The overall parasitemia clearance rate of 53.6% obtained in this study with FBE, HC, and cPCR on blood was not very different from the cure rates obtained in a previous study (60.5%) 17 that used these same techniques, classically used in cure control of CD in the past, in addition to the enzyme-linked immunosorbent assay (ELISA) test to evaluate most of these strains and suggested that a considerable proportion of animals are not parasitologically cured. Negative blood test results only indicate that the parasitemia levels were below the limit of detection of the methods used and provide no information on the parasite burden in the extravascular organs.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The overall parasitemia clearance rate of 53.6% obtained in this study with FBE, HC, and cPCR on blood was not very different from the cure rates obtained in a previous study (60.5%) 17 that used these same techniques, classically used in cure control of CD in the past, in addition to the enzyme-linked immunosorbent assay (ELISA) test to evaluate most of these strains and suggested that a considerable proportion of animals are not parasitologically cured. Negative blood test results only indicate that the parasitemia levels were below the limit of detection of the methods used and provide no information on the parasite burden in the extravascular organs.…”
Section: Discussionsupporting
confidence: 56%
“…16 The susceptibilities of these strains to BZ varied from 0% to 100%, and there was no correlation between this parameter and the DTU strain classifications, as reported previously. 17 However, TcII showed a higher proportion of BZ-sensitive strains, i.e., whose inoculated animals exhibited a sustained parasitemia clearance after treatment with BZ and TcIV resistant ones. Small differences between parasitemia clearance rates of each strain or DTU of the current study and the cure rates obtained in the previous study 17 might be caused by the developmental stages used for inoculation and the techniques used to monitor cure, and the selection (as a result of laboratory manipulation) of different genotypes that might be present within the same strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these reports evidenced that the TcI strains were usually the most resistant to trypanocidal treatment, TcII stocks presented greatly variable responses, and TcVI isolates were the most susceptible. However, these associations have not been fully confirmed by other authors [69][70][71] . Accordingly, further long-term studies are necessary to investigate this issue, especially those monitoring the treatment responses of patients with Chagas disease whose parasite DTU has been identified.…”
mentioning
confidence: 39%